Supply Chain Pessimistic Efficiency Evaluation using a Modified Data Envelopment Analysis Model - Mustapha D. IBRAHIM; Sahand DANESHVAR (International Journal of Supply Chain Management, 2017)
Supply chain efficiency evaluation is a strategic approach for organizations or business to have competitive edge in today's global market, whre it is more a competition od supply chain rather than competition of products. Time to market, customer satisfation and capital/income of the supply chain are some of the key efforts that show the efficiency of a supply chain, which determines the success of a product or organization. THe exaggeration of the performance of a supply chain is a problem of the evaluation. This exaggeration often leads to wrong forecast and shortfall of improvement. In this study a modified data envelopment analysis (DEA) model is employed to evaluate the efficiency of pharmaceutical companies in India from a pessimistic point of view. The pessimistic piont of view is considered because the worst case scenario gives management room to prepare for such events. India's pharmaceutical industry is undergoing a shift in business model according to [12] to comply with the product patent regime from 2005, this evaluation point out the weak efficient and highly inefficient Decision Making Units (DMUs), in this case twenty-nine pharmaceutical companies. A comparison is made between the efficiency of Banker, Charnes Cooper (BCC) model with modified DEA model to highlight the DMUs that are exaggerated. In addition, the weight distribution of the ten inputs and outputs used are analyzed to suggest resource allocation for performance improvement of ineffienct pharmaceutical companies.